Knowledge Level of North Andaman Farmers towards Scientific Vegetable Cultivation Practices - B.L. Kasinath, Shardul Vikram Lal, Shailesh Kumar, Pooja Kapoor, D. Basantia, B.L. Meena, Tanmai Paul, S.K. Zamir Ahmed, S. Dam Roy and A. Kundu (Indian Journal of Extension Education, 2018)
The present study was conducted in Diglipur Tehsil of North & Middle Andaman district with 120 respondentsfrom 8 villages using random sampling techniques during 2016-17. The results showed that 20 per cent offarming community belonged to youth and had medium level of annual income (47%). These socio-economicfactors were mainly attributed to their poor adoption behaviour of cultivation practices. The vegetable cultivationsignificantly contributed (50%) to the farmers’ income. Further, it was found that majority of farmers stilldepend on private dealers to redress the pest problems. The correlation analysis with farmer’s socio-economicfactors and adoption of improved cultivation practices revealed that knowledge of respondents increased withthe increase in their education and income. Educating the farmers through mass media, training anddemonstration will help the farmers in learning/adopting new technologies, which intern help them to increasetheir productivity level and their farming income on sustainable basis. Thus, it can be observed from thisstudy that age, education and farming income influence much on motivation for learning and adoption level offarmers.